The effects of Comboplow on some soil physical properties of University Putra Malaysia Research Farm - Hashemi, Ali; Ahmad, Desa (Faculty of Engineering, Universiti Putra Malaysia, 2012)
A disc plough combined with a set of rotary blades (Comboplow) for land preparation has been designed, fabricated and tested. The Comboplow includes two units of tillage tool comprising of a disc plough and several rotary blades. The disc plough cuts, partially or completely inverts a layer of soil to bury surface material. The soil in contact with the surface of disk would be cut and pulverized by the rotary blades. Multiple tillage operations are reduced to a single pass, resulting in a potential reduction of soil compaction, labour and fuel cost. The Comboplow was tested at Universiti Putra Research Farm having sandy clay loam soil texture. The treatments were three types of blades (straight type, curved and L- shaped ) and three rotary speeds (130, 147 and 165 rpm). The parameters measured were Mean Weight Diameter (dry basis), Mean Weight Diameter (wet basis), and soil bulk density. The mean weight diameters of the soil aggregates (dry basis) were 3.54, 3.28 and 3.12 mm at rotational blade speeds of 130, 147 and 165 rpm, respectively. The mean weight diameters of the soil aggregates (dry basis) were 3.21, 3.36 and 3.38 mm for the straight type blade, curved type blade and L-shaped blade, respectively. An increase in rotary speed reduced the mean weight diameter (dry basis). The mean weight diameters of soil aggregates (wet basis) were found to be 1.39, 1.66 and 1.73 mm at rotational speeds of 130, 147 and 165 rpm, respectively. The mean weight diameters of soil aggregates (wet basis) with the straight type blade, curved type blade and L-shaped blade were 1.63, 1.59 and 1.56 mm, respectively. An increase in the rotational speed from 130 to 165 rpm decreased the mean weight diameter (wet basis) by 0.34 mm. In comparison to the control treatment, the straight type blades, L-shaped blades and curved type blades decreased soil bulk density by 23.6%, 23.2% and 21.5%, respectively. The L-shaped blade had maximum and minimum values of percentage bulk density (dry basis) at rotary blade speeds of 165 and 130 rpm, respectively.